(RETRACTED) Komunitas Gastropoda di Hutan Mangrove Segara Anakan Cilacap - Moria Yunantri; Eti Wahyuningsih; Dewi Kresnasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to determine the gastropod community in the Cilacap Segara Anakan Mangrove Forest. The research was conducted in July-September in the Cilacap Segara Anakan Mangrove Forest. This study uses a survey method, sampling is carried out 3 times in July-September 2021. The sampling method is purposive random sampling. There are 3 observation stations, station 1 in the east, station 2 in the middle and station 3 in the west of the Cilacap Segara Anakan Mangrove Forest. The results of this study were 17 species and divided into 7 families, namely Potamididae, Neritidae, Littorinidae, Muricidae, Ellobiidae, Thiaridae, Assimineidae. Diversity (H') ranges from 0.45-1.06, which means that the level of diversity is in the low to medium category. High gastropod abundance was found at station 3, which was 747 individuals with 12 species. Dominance (C) with the highest index value of 0.76 which means that the level of dominance of gastropods is high and there is a dominant gastropod species, namely Melanoides tuberulata and the lowest index value of 0.36 which means that the level of dominance of gastropods is low, there is no dominant gastropod.